Fuelling change: Harnessing water hyacinth for Bio-Fuel, a catalyst for changein Hartbeespoort - Shippon, Angelique (University of the Witwatersrand, Johannesburg, 2023)
The Hartbeespoort community has long grappled with the invasive water hyacinth, a menace causing ecological and economic harm to the man-made Hartbeespoort Dam since the 1970s. After research and interviews, it’s clear that trapped pollution is the core issue, rendering conventional control methods insufficient. In response, this architectural thesis presents Fuelling Change, an innovative solution merging agro-industry, natural water purification, and tourism through 5 sub-programs. The primary objective is to transform the water hyacinth challenge into a self- sustaining ecosystem that both generates income for management and enhances water quality. This involves a digester plant to control hyacinth growth through utilization, collaborating with local farmers to establish a closed-loop nutrient cycle, and rejuvenating the social fabric with a promising Waterfront initiative. Employing an Emancipatory research approach empowers the community, while integrating critical regionalism and biophilic design ensures authenticity and alignment with the area’s identity. The proposed design converts an ecological crisis into a catalyst for positive change, fostering socio-economic regeneration in Hartbeespoort. Agro-industry: industry connected with agriculture. Emancipatory research: define & add to list [ ii ] ABSTRACT
A research report submitted in fulfillment of the requirements for the Masters in Architecture, In the Faculty of Engineering and the Built Environment, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: UCTD; Pollution contro; Water purificatio; Ecological restoration; SDG-7: Affordable and clean energy; SDG-6: Clean water and sanitation